Harmonization of legal regulation of consumers’ relations - M. M. Kletchenkova (Московский журнал международного права)
One of the trends of the legislative development in the field of regulation of relations with participation of consumers last decades in the world is process of its harmonization. Most widely and consistently this process occurred within the European Economic Community (subsequently – European Union): beginning in 1973 on creation of Consumer Protection Advisory Committee, it continues till now. From the beginning of activity of EEC bodies in the field of the consumer protection the general program documents in the given sphere, and then statutory acts in the form of EEC (EU) Directives have appeared. Council of EU accepted statutory acts about safety and quality textile, articles of food, dangerous to life and health the substances, promoting creation of a civilized commodity market, works and services. At EU the uniform normative basis and the mechanism of its realization for consumer protection is created with the help of means of harmonization.To an urgency of this tendency with reference to the Russian legislation in the field of consumer protection and to those of the CIS it was paid attention even from the moment of acceptance in 1992 of the Consumer protection Act. Harmonization within the CIS is shown in conclusion the treaties at a bilateral or multilateral level (with the Kirghiz Republic, Ukraine), resolutions on results of the international conferences on questions of the consumer right.Culmination and simultaneously final moment of scientists’ and practitioners’ efforts within the CIS is the conclusion the basic unified document – Agreements on the basic directions of cooperation of the Member States of the Commonwealth of Independent States in the field of consumer protection from January, 25, 2000 which purpose is creation of legal and organizational bases of cooperation of the Parties on realization of systematic policy in the sphere of the consumer protection directed to formation of equal conditions for citizens of the Member States of Commonwealth on protection of their interests from unfair activity of managing subjects.In summary it is necessary to note, that within the CIS the level of uniform legislative fixation of general rules of consumer protection is not achieved yet: the uniform modeling law on protection of the consumers which could be implement in legislations of the Member States of the CIS is not concluded. As consequence of it there are also problems applications of law: process of an establishment the contents of the foreign law, even legislations of the countries of the CIS, causes known difficulties. In this connection, the perspective of litigation with use of the foreign law quite often induces the parties to refuse of dispute, to make a peace settlement of dispute, or to universal apply the law of the country of court.